2011
DOI: 10.1007/s11738-010-0705-5
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of Prosopis laevigata (Humb. & Bonpl. ex Willd) M.C. Johnst. cell suspension culture: a biotechnology approach for mesquite gum production

Abstract: This study presents a protocol for the establishment of Prosopis laevigata cell suspension culture as a strategy to obtain an in vitro mesquite gum productive cell line. The callus used for this purpose was obtained with hypocotyls from 15-day-old plantlets, placed on Murashige-Skoog medium with two different plant growth regulators (PGRs), 2,4,5-trichlorophenoxy acetic acid (2,4,5-T; 5.0 lM) and kinetin (KIN; 5.0 lM). With this PGRs treatment, after four subcultures (30 days each) an exuded gum-like substance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…In other Fabaceae species such as Prosopis laevigata , the in vitro germination can occur after 3–7 days in mechanically scarified seeds [ 14 , 15 ]. Regarding callus induction, a suitable response of callus formation was exhibited on internodal segments after 15 days of culture ( Figure 1 B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other Fabaceae species such as Prosopis laevigata , the in vitro germination can occur after 3–7 days in mechanically scarified seeds [ 14 , 15 ]. Regarding callus induction, a suitable response of callus formation was exhibited on internodal segments after 15 days of culture ( Figure 1 B).…”
Section: Resultsmentioning
confidence: 99%
“…It is known from callus induction treatments on semisolid culture medium that these do not always adapt best to a liquid culture medium. For instance, P. laevigata leaf explants presented 100% of callus with trichlorophenoxyacetic acid (2,4,5-T, 1.28 mg/L) with BAP (1.13 mg/L) or 2,4,5-T (1.28 mg/L) with KIN (1.08 mg/L); however, only calluses containing KIN were suitable for establishing the CSC [ 14 ]. This indicates that, even among closely related species, the genotype is an influential factor in the response of cell cultures; moreover, the PGRs activity varies depending on the presence of transporter or receptor biosynthesized proteins in the explants, affecting in vitro culture development [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The duplication time (t d ) was 14.1 days, and specific growth rate (µ) was 0.049 days −1 . However, studies conducted by Trejo-Espino et al (2011) in a Prosopis leavigata cell suspension culture reported a lower MAB (11.9 g DW L −1 ). Instead the t d (6.6 days) and µ (0.104 days −1 ) were higher than those found in this study.…”
Section: Growth Kinetics Of Cell Suspension Culturesmentioning
confidence: 88%
“…La combinación de 1.5 mg L -1 de 2,4-D con 1.0 mg L -1 KIN (D1.5K1.0) o con BAP (D1.5B1.0) presentaron significativamente el mayor porcentaje de inducción de callo (100%) así como las mejores características de friabilidad y rápido crecimiento (Tabla 6). En los reportes existentes para la inducción de callo en especies relacionadas, P. juliflora (Nandwani y Ramawat, 1991), P. tamarugo (Nandwani y Ramawat, 1991) y P. laevigata (Trejo-Espino et al, 2011), ha sido necesario el uso de la combinación de auxinas y citocininas para la obtención de callo. La inducción de callo se vio significativamente afectada por el tipo de explante (cotiledón, hipocótilo y raíz).…”
Section: Inducción De Callounclassified
See 1 more Smart Citation